GREEN LIBRARIES IN ACADEMIC INSTITUIONS: NEED OF THE HOUR - Shah, Leena; Kumar, Sudhir; Kumar Shah, Mukesh (International Journal of Research -GRANTHAALAYAH, 2015)
Explains term “Green” and special challenges met by libraries to be Green. Points out steps involved such as site selection, water and energy conservation, building material and indoor air quality. Briefly narrates few green libraries initiatives such as Fayetteville Public Library, Minneapolis (2004), Seattle Central Library (2004), National Library, Singapore (2005), Minneapolis Public Library (2006), and University of California (2005). Also discusses steps taken by TERI in developing GRIHA. Suggests for proper planning of buildings with solar energy system and roof water harvesting, etc.